2020
DOI: 10.1038/s41467-020-18130-3
|View full text |Cite|
|
Sign up to set email alerts
|

A role for Biofoundries in rapid development and validation of automated SARS-CoV-2 clinical diagnostics

Abstract: The SARS-CoV-2 pandemic has shown how a rapid rise in demand for patient and community sample testing can quickly overwhelm testing capability globally. With most diagnostic infrastructure dependent on specialized instruments, their exclusive reagent supplies quickly become bottlenecks, creating an urgent need for approaches to boost testing capacity. We address this challenge by refocusing the London Biofoundry onto the development of alternative testing pipelines. Here, we present a reagent-agnostic automate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 27 publications
(35 reference statements)
0
61
0
Order By: Relevance
“…In projects where high-throughput, reproducible results are demanded over short time frames automation has significant advantages over manual procedures. Recently a highly automated biofoundary, normally with a focus on research applications, was repurposed towards the development of SARS-CoV-2 assays for clinical diagnostics (Crone et al, 2020). Automated liquid handling equipment was able to perform an extensive array of experimental procedures at a rate in excess of those that a manual based laboratory could carry out.…”
Section: Examples Of Automation Benefitsmentioning
confidence: 99%
“…In projects where high-throughput, reproducible results are demanded over short time frames automation has significant advantages over manual procedures. Recently a highly automated biofoundary, normally with a focus on research applications, was repurposed towards the development of SARS-CoV-2 assays for clinical diagnostics (Crone et al, 2020). Automated liquid handling equipment was able to perform an extensive array of experimental procedures at a rate in excess of those that a manual based laboratory could carry out.…”
Section: Examples Of Automation Benefitsmentioning
confidence: 99%
“…The approach chimes with the distributed supply chains and distributed manufacturing that could be transformative in dealing with COVID-19 and future pandemics throughout the world. The potential of the approach was demonstrated by Crone and co-workers [ 22 ] who showed that an automated SARS-CoV-2 clinical diagnostics platform designed and developed in a biofoundry can be quickly deployed and scaled.…”
Section: The Synthetic Biology Approach Lends Itself To a Distributedmentioning
confidence: 99%
“…The recently formed Global Biofoundries Alliance [ 23 ] has publicly funded biofoundries in North America, Europe, Asia, and Australia, which could be brought to bear for the design of new vaccines, as needed. As pointed out by Crone and co-workers [ 22 ], the protocols and workflows they developed can be quickly incorporated and modified as necessary by members of the Global Biofoundry Alliance. Box 2 shows front-running approaches to vaccine production that are highly amenable to the synthetic biology approach.…”
Section: The Synthetic Biology Approach Lends Itself To a Distributedmentioning
confidence: 99%
“…163 Obviously, continued development of these processes will enable better evaluation of how RT-LAMP holds up relative to other strategies, but initial reports are encouraging. 164 However, the low technical requirements render this strategy applicable to low technology level areas that are in need of rapid and cheap tests that are simple to run. It should be noted that one issue with such strategies is product contamination across samples, although some approaches have been proposed to minimize this issue.…”
Section: Reverse Transcription Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%